2019
DOI: 10.1002/ccr3.2172
|View full text |Cite
|
Sign up to set email alerts
|

A case of inflammatory pseudotumor of the lung presenting as polymyalgia rheumatica

Abstract: A common inflammatory condition, the investigation and diagnosis of polymyalgia rheumatica should be within the scope of a general physician's repertoire. While there is limited evidence to confirm the existence of polymyalgia rheumatica as a distinct paraneoplastic syndrome ( Reumatismo . 2018; 70 (1):23), a broadened differential should be utilized prior to diagnosis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…11,18 Tompkins et al and Kato et al have previously reported on a patient with IPT of the lungs and thoracic spine, respectively, with underlying polymyalgia rheumatica. 19,20 There are no reports on patients with polymyalgia rheumatica and hepatic IPT. In our patient, we did not find any other underlying causes, which could have led to an IPT of the liver except for her polymyalgia rheumatica.…”
Section: Discussionmentioning
confidence: 99%
“…11,18 Tompkins et al and Kato et al have previously reported on a patient with IPT of the lungs and thoracic spine, respectively, with underlying polymyalgia rheumatica. 19,20 There are no reports on patients with polymyalgia rheumatica and hepatic IPT. In our patient, we did not find any other underlying causes, which could have led to an IPT of the liver except for her polymyalgia rheumatica.…”
Section: Discussionmentioning
confidence: 99%